Note on the type, identification and type locality of Quercus oblongifolia var. pallidinervis (Fagaceae) in Chihuahua - Spellenberg, Richard (Instituto de Ecología, A.C., 1990)
Cuando Trelease described the variety Quercus oblongifolia Torr. var. pallidinervis Trel. He indicated that the type was photographed in “Washington”, but the specimen that he illustrated was recently discovered to be in the Gray Herbarium. It is considered to be the holotype; a different specimen from the same collection resides in the US National Herbarium and is considered to be an isotype. Based on recent collections and the literature, the variety is determined to be a synonym of Quercus depressipes Trel. And its type locality to be in the Sierra de la Breña in northwestern Chihuahua.